Integrating gender in forage systems research - Peters, Michael (International Livestock Research Institute, 2016)
Gender is crucial for research on forages. We need to look at at gender aspects of forage production, such as labour-conservation techniques that may affect women and youth the most. Women and youth may have opportunities in feed processing and in forage-seed production. We also need to understand how technology changes affect gender relations. Once a technology becomes more commercially oriented, gender roles may be affected, resulting in unexpected or undesirable effects. Interview with Michael Peters (CIAT) for the book "A different kettle of fish? Gender integration in livestock and fish research". http://hdl.handle.net